Asimilasi Animisme Dalam Kegiatan Tahlilan: Studi Dakwah Bil’ Hikmah Di Kecamatan Siompu Barat - Wa Ode Fatmawati; Ardiansyah Ardiansyah (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2023)
After the spread of Islam in the Buton islands brought by Sheikh Abdul Wahid for the second time in 1948 H. Then the intellectuals or Islamic intellectuals who came from Buton. Taking the initiative to develop teachings throughout the coastal areas of Buton, especially on the western coast of Siompu Island, where one of the teachings is teaching about tahlilan. The purpose of this study was to find out how the community understands the tahlilan tradition in West Siompu sub-district? And to find out the method of preaching Bil' wisdom in understanding the tahlilan tradition in Siompu Barat sub-district? Data collected using data collection methods, namely: observation, interviews and documentation methods. The results of this study can be recommended for further research on the history of Buton. In particular, the western Siompu area. As an effort to add a little reference and knowledge about the history of the arrival of Islam in the land of Buton.